Factores de riesgo de litiasis renal en pacientes atendidos en el Centro de Salud Zapotillo 24 HD. - Quintanilla Barba, Karin Yesenea (2017)
Renal Lithiasis is multifactorial illness which constitutes a health public problem in the canton of Zapotillo, in which epidemiological, racial, dietetic, geographical and hereditary aspects have been involved. The following investigation was released with the objective to determine the amount of cases with renal lithiasis and its relationship with risk factors on patients that have been attended at “Centro de Salud Zapotillo 24 HD (hours a day)”. This is a quantitative study, exploratory, correlational; this was carried out by 400 people that were attended during the period of June-September 2016. The correlation of the information was released through a survey; obtaining among the most significant data, that the higher number of cases from renal lithiasis is found on people between 35 to 45 years of age on a 63%, and affecting the male genre on a 70%. Its main risk factors the consumption of dairy products (goat's milk) by 35%; followed by low water intake in 26%. Therefore, it is concluded that in the study population there are a large number of cases of renal lithiasis, all of which are attributed to lack of fluid plus inadequate or excessive dietary habits. With the results obtained not only support the right data for the creation of future projects and investigations, it will also allow to implement future measurements on modified factors, allowing to improve the quality of life for the patient and their families. Key-words: risk factors, renal lithiasis